Yield and physical-chemical quality of table olives in different hedgerow canopy positions (cv. Manzanilla de Sevilla and Manzanilla Cacereña) as affected by irradiance - Rallo, Pilar (2023)
Unlike olive orchards intended for olive oil, the production of table olives in narrow hedgerows is very recent and the information available about this cropping system is yet very scarce. In this work, we studied for the first time in table olive hedgerows (3.75m x 1.35m, N-S oriented) of Manzanilla de Sevilla and Manzanilla Cacereña cultivars, the distribution within the canopy of yield components and physical-chemical fruit quality traits in response to the incident irradiance. Hedgerow canopies were divided into four positions on each side (East and West) according to height aboveground: 0.5–1.0m, 1.0–1.5m, 1.5–2.0m, 2.0–2.5m, and an additional top canopy position (> 2.5m) integrated for both sides. Total production, number of fruits and size distribution were recorded for each position and the following fruit traits were assessed: fresh weight, length, equatorial diameter, pulp-to-pit ratio, color index, bruising percentage, oil content, water content, total sugars and total phenols. Individual phenolic compounds were also quantified. The incident irradiance at each position was calculated over the fruit growth period using a model based on hedgerow parameters, resulting in a positive gradient from base to top canopy positions. For both cultivars, yield components and most quality traits were positively affected by incident irradiance as they followed a similar trend showing larger mean values with increasing canopy heights. Conversely, the total contents in sugar and phenols and individual phenolic compounds were not affected by the canopy positions. No remarkable differences between East and West sides of the hedgerow were observed.